2015
DOI: 10.3390/s150921857
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Sensor Data Fusion Using a Relevance Vector Machine Based on an Ant Colony for Gearbox Fault Detection

Abstract: Sensors play an important role in the modern manufacturing and industrial processes. Their reliability is vital to ensure reliable and accurate information for condition based maintenance. For the gearbox, the critical machine component in the rotating machinery, the vibration signals collected by sensors are usually noisy. At the same time, the fault detection results based on the vibration signals from a single sensor may be unreliable and unstable. To solve this problem, this paper proposes an intelligent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…Firstly, the SVADS system concludes multiple pressure measuring channels, and each channel has complex faults modes such as the blockage of pressure ports, pipe pressure leak, faults of pressure sensors and faults of circuits; secondly, the faults feature of each mode is nonlinear, which the difficulty in faults feature extraction is bigger; thirdly, the mount of actual faults data is very little, and the small sample problem needs to be solved; lastly, the obtained fault information includes some uncertain extent and the classification results should be uncertain. Presently, some faults diagnosis algorithms have been proposed based on empirical mode decomposition (EMD) [10], neural networks [11], and relevance vector machine (RVM) [12]. Based on the adaptive decomposition of signals in frequency domain, EMD has applied to some feature exaction; however, its mode mixing problem is not suitable for nonlinear faults feature exaction of this paper.…”
Section: Figure 1 Construction Models Of Svads Systemmentioning
confidence: 99%
“…Firstly, the SVADS system concludes multiple pressure measuring channels, and each channel has complex faults modes such as the blockage of pressure ports, pipe pressure leak, faults of pressure sensors and faults of circuits; secondly, the faults feature of each mode is nonlinear, which the difficulty in faults feature extraction is bigger; thirdly, the mount of actual faults data is very little, and the small sample problem needs to be solved; lastly, the obtained fault information includes some uncertain extent and the classification results should be uncertain. Presently, some faults diagnosis algorithms have been proposed based on empirical mode decomposition (EMD) [10], neural networks [11], and relevance vector machine (RVM) [12]. Based on the adaptive decomposition of signals in frequency domain, EMD has applied to some feature exaction; however, its mode mixing problem is not suitable for nonlinear faults feature exaction of this paper.…”
Section: Figure 1 Construction Models Of Svads Systemmentioning
confidence: 99%
“…As aforementioned, in the proposed work, the acquired vibrations signals belong to those vibrations in the perpendicular plane of the gearbox rotating axis since some studies has reported that the occurrence of perpendicular vibrations on the rotating axis is related to the inappropriate working conditions of rotational machines [5], [13], [24]. Regarding the proposed methodology, the data acquisition is performed by carrying out different experiments at different operating frequencies for driving the induction motor: 5 Hz, 15 Hz and 50 Hz.…”
Section: Validation Of the Methodsmentioning
confidence: 99%
“…Despite their reliability, the appearance of unexpected faults in gearboxes may occur at any time, causing unscheduled breakdowns in the elements of the associated kinematic chain. It has been reported that the appearance of gear faults account for 80% of the breakdowns in transmission machinery systems and 10% of the faults in rotating machinery [4]- [5]. Therefore, strategies of condition monitoring and fault detection related to gearbox transmission systems play a key role to ensure the effectivity and safety of multiple industrial processes [6]- [8].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, widely-used mechanical fault prediction methods employ artificial neural networks (ANNs) [4][5][6], support vector machines (SVMs) [7,8], deep learning [9][10][11], and other artificial intelligence (AI) technologies. For example, Ben et al [12] proposed the use of empirical mode decomposition and energy entropy for feature extraction, which was combined with an ANN for multifeature fusion to make bearing fault predictions.…”
Section: Introductionmentioning
confidence: 99%